TAZ promotes the proliferation and osteogenic differentiation of human periodontal ligament stem cells via the p‐SMAD3. Issue 2 (3rd September 2019) - Gu, Ke; Fu, Xucheng; Tian, Hui; Zhang, Yafei; Li, Aonan; Wang, Ying; Wen, Yong; Gu, Weiting
Abstract: Objective: This study aims to offer insights about the biological influence of TAZ, which is a transcriptional coactivator containing a PDZ‐binding motif, upon the apoptosis, proliferation, and osteogenic differentiation of human periodontal ligament stem cells (h‐PDLSCs). Methods: We used the green fluorescence protein lentivirus infection system to knockdown or overexpress TAZ in h‐PDLSCs. 5‐ethynyl‐2'‐deoxyuridine (EdU) staining detected the proliferative activity, and h‐PDLSC apoptosis was analyzed by Annexin V‐APC staining. TAZ knockdown or overexpression was performed to determine the osteogenic differentiation function of TAZ during the osteogenic induction of h‐PDLSCs. The molecular mechanism of TAZ in the promotion of h‐PDLSC osteogenesis was also explored. The chemical inhibitor of SMAD2/3 SIS3 HCL was used to identify the effects in vitro osteogenic differentiation and bone formation in h‐PDLSCs overexpressing TAZ. Results: TAZ overexpression resulted in enhanced cell rapid multiplication, which increased the expression of messenger RNA in stemness‐related genes. By comparison, TAZ knockdown reduced proliferative activity and increased the apoptosis of h‐PDLSCs. After the 7‐day osteogenic induction period, alkaline phosphatase activity in the TAZ‐overexpression group was significantly increased, and mineralized nodules increased significantly after osteogenic induction for 21 days. Similarly, osteoblast differentiation of h‐PDLSCs was impaired after TAZ knockdown. However, the osteogenic potential of the group exposed to the p‐SMAD3 inhibitor was restored to its original level. Conclusion: Hippo/TAZ plays a positive role inside the proliferation, stemness maintenance, and osteogenic specialization of h‐PDLSCs, and the specific downstream factor of osteogenic differentiation is SMAD3. Abstract : The purpose of this study was to provide insights into the biological effects of TAZ, a transcriptional coactivator containing a PDZ‐binding motif, on the proliferation, apoptosis, and osteogenic differentiation of human periodontal ligament stem cells.